Potenziale von Bildern beim Kulturbezogenen Lernen : eine empirische Studie zu Deutschlehrenden und ägyptischen Lernenden - Elshehawy, Mohammed (Brünner Beiträge zur Germanistik und Nordistik, 2023)
This article addresses the question of the extent to which ambiguous images with cultural potential play a role in culture-related learning processes. It is assumed that images with multiple interpretations can have a high potential in the culture-related learning field, which leads learners to express their feelings and emotions more strongly. The concepts of interpretation learning by Ingeborg Schüßler, the concept of emotion learning by Rolf Arnold, and the theory of expansive learning by Klaus Holzkamp with his subject position serve as the theoretical basis for concretizing the concept of culture-related learning in this work. This work is also based on the cultural studies approach of discursive cultural studies by Claus Altmayer, in which "culture" is no longer defined objectively, but as a negotiation of meanings. This work attempts to find answers to the following questions based on an empirical investigation of German teachers in Egypt and Egyptian German as a Foreign Language learners: To what extent can images initiate the culture-related learning process? What potentials do images have on the different levels within culture-related learning processes?